Energy Efficiency as a Way to Ecological Safety: Evidence From Russia - Denisova, Valeriia (International Journal of Energy Economics and Policy, 2019)
The paper proposes the link between effective use of energy and reduction of carbon emissions at the case of Russia. A number of energy efficiency indicators are reviewed and calculated. Deterministic analysis is conducted to identify what factors influence carbon intensity the most. The analysis has shown that increasing energy intensity causes a much greater increase in carbon intensity. This paper adopts the method of chain substitutions to calculate the contribution of each factor to the changes in the carbon intensity over a period of time. Therefore, it must be the ultimate goal to achieve a sustainable economy by consuming less energy which in its turn will lead to less CO2 emission. Keywords: energy consumption, energy efficiency, carbon intensity, method of chain substitutions. JEL Classifications: Q40, Q43, O44, O52 DOI: https://doi.org/10.32479/ijeep.7903